Reflexiones sobre el espacio geográfico - Miralbés Bedera, Rosario; Higueras Arnal, Antonio (Geographicalia, 2017)
For centuries the essence of geographical knowledge did not present any doubts: it was about getting to know the world, discovering new lands, peoples and cultures. Man had a curiosity to know what laid beyond his ownsurroundings. But today the entire world is known to man. That is why the subject of geographical studies has changed. At present, the work of geographers consists of researching into the organisation of space and its a attributes, always bearing in mind that every spatial area forms a part of a territorial system.
Keywords: Geographical space.